Unlocking lending in Europe - Tim Bending; Markus Berndt; Frank Betz; Philippe Brutscher; Oskar Nelvin; Debora Revoltella; Tomas Slacik; Marcin Wolski (European Investment Bank (EIB), 2014)
In the wake of the crisis, the capacity of many banks to lend to relatively high-risk sectors such as SMEs and young, innovative firms is seriously impaired by capital constraints and a strong deterioration in the quality of the assets on their balance sheets. Looking forward, it is vital that economic recovery in Europe is not constrained by an impaired banking sector. This paper provides an overview of the drivers of the stagnation of bank lending in Europe and discuss four main areas of opportunity for mitigating potential bank lending constraints: the further development of direct capital market financing alternatives for firms, the further development of securitisation, wider use of credit guarantee schemes and actions to address high ratios of non-performing loans.
Keywords: 330; KMU; Unternehmensgründung; Unternehmensfinanzierung; Kreditrationierung; Kreditgeschäft; Bürgschaftsbank; Verbriefung; Notleidender Kredit; EU-Staaten